Impact of Laser Correction on the Hydrant Envelop of Biological Structures of Myocytes and Hepatocytes in Massive Blood Loss - V. L. Kozhura; S. S. Nikolayeva; A. A. Roshchina; A. K. Kirsanova; L. V. Yakovleva; V. A. Bykov; I. S. Novoderzhkina; L. B. Rebrov; Ye. Yu. Parshina (Общая реаниматология)
Acute rat experiments have studied the impact of acute blood loss on the distribution of water fractions (total, free, and bound) in myocardial and hepatic tissues and whether detected impairments can be corrected by laser irradiation. They have provided an insight into the new pathogenetic mechanisms responsible for homeostatic disorders in blood loss and some aspects of the mechanism of action of laser emission on the body’s adaptive processes. The functioning of biopolymers and molecular structures in tissues is largely determined by their content of water. The redistribution of water towards to a blood loss-associated increase in bound water is a compensatory reaction aimed at preserving the biological structure of biopoly-mers. The decrease in hydrant-bound water suggests that there are severe derangements of their structure. The changes in the tissue free/bound water ratio reflect the degree of the body’s dysadaptation to blood loss. Laser irradiation has an adap-togenic effect on the structure of water in compensated hemorrhagic shock and a damaging action in decompensated one.